2022
DOI: 10.1021/acs.iecr.2c01587
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane-Coated Nanoparticles for Management of Infectious Diseases: A Review

Abstract: Infectious diseases have emerged as leading threats to global healthcare, such as bacterial and viral infections. Major challenges in combating these infectious diseases are the emergence of adverse effects during the long-term use of anti-infectious drugs and the increasing prevalence of drug resistance. Cell membrane-coated nanoparticles have great potential in the prevention and therapy of infectious diseases. This promising therapeutic strategy is to employ cell membrane-based nanoparticles as a decoy to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…Apart from the several innovative and commonly used preparation methods mentioned above, other novel methods for the encapsulation of nanoparticles into cell membranes have been reported. Freeze–thaw/sonication, extrusion/sonication and stirring, extrusion/electroporation, and in situ packaging methods have also been successfully applied in coating cell membranes on the surface of nanomaterials. ,, Collectively, the extracted cell membrane can be employed in analyzing various substances directly in the form of vesicles or to prepare cell membrane-coated nanoparticles using membrane coating technology for bioanalysis.…”
Section: Common Preparation Methods For Extracted Cell Membrane-based...mentioning
confidence: 99%
“…Apart from the several innovative and commonly used preparation methods mentioned above, other novel methods for the encapsulation of nanoparticles into cell membranes have been reported. Freeze–thaw/sonication, extrusion/sonication and stirring, extrusion/electroporation, and in situ packaging methods have also been successfully applied in coating cell membranes on the surface of nanomaterials. ,, Collectively, the extracted cell membrane can be employed in analyzing various substances directly in the form of vesicles or to prepare cell membrane-coated nanoparticles using membrane coating technology for bioanalysis.…”
Section: Common Preparation Methods For Extracted Cell Membrane-based...mentioning
confidence: 99%
“…Cell membrane-coated NPs possess prospects in antiviral therapy. 80 Despite recent advancements in treatment, HIV type-1 infection is still fatal. Eliminating the virus is challenging because of the presence of residual viruses that evade therapy.…”
Section: Viral Infectious Diseasesmentioning
confidence: 99%
“…The utilization of combination antiretroviral therapy is wide-ranging, but the emergence of resistance and the difficulties associated with long-term medication pose significant challenges to traditional therapies. Cell membrane-coated NPs possess prospects in antiviral therapy …”
Section: Viral Infectious Diseasesmentioning
confidence: 99%
“…The liposomes loaded with chloroquinoline effectively transferred the drugs, inhibiting parasite growth. Furthermore, combination therapy encapsulates antiparasitic medications with immune modulators, improving treatment outcomes and enhancing bioavailability and therapeutic value [145]. Accordingly, Moles and his research group [85] confirmed immuno-PEG-liposomes for targeted drug delivery in a murine malaria model, efficiently encapsulating amphiphilic drugs like chloroquine and primaquine using a pH gradient.…”
Section: Organic Nmsmentioning
confidence: 99%